Superconductivity of compressed iron: Low temperature electrical transport behaviour - Pedrazzini, Pablo (2010)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of Geneva; Suiza